Characterization and regulation of the gene encoding nitrite reductase in Rhodobacter sphaeroides 2.4.3. - Tosques, I E (1997)
Nitrite reductase catalyzes the reduction of nitrite to nitric oxide, the first step in denitrification to produce a gaseous product. We have cloned the gene nirK, which encodes the copper-type nitrite reductase from a denitrifying variant of Rhodobacter sphaeroides, strain 2.4.3. The deduced open reading frame has significant identity with other copper-type nitrite reductases. Analysis of the promoter region shows that transcription initiates 31 bases upstream of the translation start codon. The transcription initiation site is 43.5 bases downstream of a putative binding site for a transcriptional activator. Maximal expression of a nirK-lacZ construct in 2.4.3 requires both a low level of oxygen and the presence of a nitrogen oxide. nirK-lacZ expression was severely impaired in a nitrite reductase-deficient strain of 2.4.3. This suggests that nirK expression is dependent on nitrite reduction. The inability of microaerobically grown nitrite reductase-deficient cells to induce nirK-lacZ expression above basal levels in medium unamended with nitrate demonstrates that changes in oxygen concentrations are not sufficient to modulate nirK expression.